Challenges and acceptance of the use of computer-assisted personal interviews technology for verbal autopsy/social autopsy child mortality survey in urban slums of Karachi, Pakistan. - Siddiqui, Muhammad Bilal; Wan Ng, Chiu; Wah Yun Low; Noushad , Shamoon; Ahmed , Sadaf; SherShah Syed (International Journal of Endorsing Health Science Research, 2018)
Background: For collecting data regarding child mortality, the verbal autopsy/social autopsy (VASA) surveys involves lengthy questionnaires. Use of computer-assisted personal interview (CAPI) technique is now preferred over paper-and-pencil interviews (PAPI) due to several factors. This study identifies the level of acceptance of CAPI over PAPI among participants; challenges in implementing this technology; and the persuading factors for improving the acceptance of and getting quality data from CAPI based VASA surveys. Methodology: This qualitative study involved a total of 20 face-to-face VASA interviews conducted from mothers of deceased under-five children in selected urban slums of Karachi, followed by semi-structured focus group discussions (FGDs) and in-depth interviews (IDIs), enquiring about their acceptance towards CAPI and discussing the challenges faced during the use of PAPI versus CAPI. Total of 8 IDIs were conducted from different stakeholders for strengths, weaknesses, opportunities, and threats (SWOT) analysis on the CAPI implementation. Thematic analysis was conducted. Results: Out of 20 female respondents (median age 28.2 years and median education 5th grade); and 10 female interviewers (median age 30.1 years and median education of 11th grade), 78.1% and 83.7% respectively were mobile phone skilled in priori. The overall outcome showed a positive acceptance (90%) of CAPI by participants. Respondents and interviewers accepted CAPI over PAPI, while the technique had some challenges as identified by different stakeholders. Conclusion: Researchers pondering the use of CAPI for VASA surveys on child mortality must consider discussed factors in order to increase the participants’ acceptance level, maximizing the involvement of CAPI in child health surveys and to obtain a quality data, especially from developing countries.